Multicomponent crystals: Solubility enhancement of simvastatin using arginine and glycine coformers - Iyan Sopyan; Karyn Elizabeth; Sandra Megantara; Silmy Kaffah (GarVal Editorial Ltda., 2024)
Context: Simvastatin can be modified by the formation of multicomponent crystals to increase its solubility. Aims: To compare the solubility of multicomponent simvastatin crystals to pure simvastatin. Methods: The in silico study of simvastatin and the coformers arginine and glycine revealed non-covalent interactions, so multicomponent preparations of simvastatin crystals were prepared by solvent evaporation using a mole ratio of 1:1; 1:2 and 2:1. Results: Each simvastatin-arginine and simvastatin-glycine ratio increased the solubility, with the highest increase observed for the 1:2 ratio compared to pure simvastatin. Conclusions: Simvastatin-arginine multicomponent crystals (1:2) showed the best dissolution profile in phosphate buffer medium pH 7.0 with 67.69% dissolution, while simvastatin-glycine multicomponent crystals (1:2) exhibited the best dissolution profile in buffer media pH 1.2 with 16.19% dissolution. Characterization of the multicomponent crystals revealed a shift in the peaks, a decreased melting point, and enthalpy, indicating decreased % crystallinity and the formation of a new solid phase.